Analysis of the principles of good corporate governance accountability and responsibility for the ministry of cooperatives in the case of the Indosurya savings and loan cooperative - Rizki Amalia Saniy Soeprapti; Muhammad Rizal; Tetty Herawaty (Enrichment : Journal of Management, 2023)
This study aims to determine the results of the analysis of the principles of Good Corporate Governance accountability and responsibility carried out by the Ministry of Cooperatives on supervising the performance of the Indosurya Savings and Loans Cooperative. The case of the Indosurya Savings and Loan Cooperative is the largest cooperative fraud case in Indonesia. It is necessary to analyze the performance of cooperative supervisory institutions and tighten cooperative regulations so that people are protected and similar cases do not recur. The research method used is descriptive qualitative. The analysis uses the principles of Good Corporate Governance, among othersaccountability and responsibility. As a result, the Ministry of Cooperatives neglected to oversee the performance of the Indosurya Savings and Loans Cooperative.